Postaxial polydactyly of the hand in Japanese patients: Case series reports. Issue 7 (July 2019) - Ishigaki, Tatsuya; Akita, Shinsuke; Suzuki, Hiroyuki; Udagawa, Akikazu; Mitsukawa, Nobuyuki
Summary: Purpose: The incidence of postaxial polydactyly of the hand is rare in Japan. This study aimed to compare the clinical presentation of postaxial polydactyly between a cohort of patients from Japan and those from other racial and ethnic backgrounds. Methods: In this retrospective study, we included 30 patients who were treated at our hospital during a 25-year study period (1990–2015). Based on the clinical records of these patients, we characterized the Japanese presentation of the condition. We searched for studies that included other racial and ethnic groups and characterized the clinical presentations. Then, we compared the clinical presentations between Japanese patients and other racial and ethnic groups. Results: A total of 19 male and 11 female patients were treated in our hospital, and bilateral and unilateral involvements (right side: 4 patients; left side: 4 patients) were observed in 22 and 8 patients, respectively. Moreover, 22 postaxial polydactylies were type A and 28 polydactylies were type B, which were classified using the Temtamy–McKusick classification system. In addition, 4 patients had a family history of hand postaxial polydactylies; 18, 6, 4, and 3 patients presented with polydactyly of the foot, syndactyly, systemic abnormalities, and related syndromes, respectively. Conclusion: Japanese patients had two distinguishing characteristics: (1) when the condition was unilateral, left side and right side involvement was almost equal with regard to incidence and (2) associated polydactylies of the foot were more common (60%) than those in other cohorts (less than 31%). To better understand postaxial polydactyly of the hand, guidelines to record the clinical presentations in patients with such a condition must be developed.